Examining the Indonesia and Malaysia student-athletes coping strategy in sports - M. S., Omar Fauzee; Don, Yahya; Susterna, Nina; Saptra, Yudha M .; Hanif, Sofyan; Abdullah, Nagoor Meera; Shahril, Mohd Izwan (European Scientific Institute, 2014)
The purpose of this paper is to compare the coping strategies among university student-athletes between Indonesia and Malaysia.A sample of 469 students athletes of Indonesia (226: female-69; male-157) and Malaysia (243: female-95; male-148) were randomly selected as the sample for this study.The age for Indonesia student-athletes (M=21.05, sd=2.31) and Malaysia student athletes (M=21.41, sd=2.50).The samples were selected from four major universities in Indonesia and Malaysia. Of the sample, 2.6% of Indonesian and 2.3% of Malaysian representing National team and 4.3% of Indonesian and 5.8% of Malaysian student-athletes representing state level during their study.However, 3.8% and 13.9% of Indonesian sample representing National and state during their high school year, respectively, 8.5% and 21.7% of the Malaysian sample representing National and state team during their high school year.The instrument used in this study was The Athletic Coping Skills Inventory (ACSI-28).Results show that there are significantly difference between Indonesia and Malaysia athletes in coping in adversity, concentration, mental preparation and goal setting, peaking under pressure and freedom from worries.Out of that, the Indonesian student-athletes score higher than Malaysian student-athletes in subthemes of freedom from worries.While, the others the Malaysia student-athletes score higher. Results were further discussed and recommended for future research.